Genetic pattern and gene localization of polydactyly in Beijing fatty chicken - He, Chuan; Chen, Yongcan; Yang, Kaixuan; Zhai, Zhengxiao; Zhao, Wenjing; Liu, Shuyun; Ding, Jinmei; Dai, Ronghua; Yang, Lingyu; Xu, Ke; Zhou, Zhenxiang; Gu, Caiju; et al. (PLOS ONE, 2017)
Polydactyly, a common heritable limb malformation in vertebrates, is characterized by supernumerary digits. In chickens, basic characteristics and rough dominant genes have been explored in past decades; however, the elaborate pattern of inheritance and the determinant gene remain obscure. In this study, different types of polydactylism were classified by the numbers and the shapes of toes, including the newly defined subtypes of B’ and G, for the Beijing fatty chicken, a native breed of chicken from China. Through experiments on hybridization, we demonstrated a complete dominant inheritance of polydactyly instead of an incomplete penetrance or genetic modification of the previous conjecture. In particular, by using the F2 population of the five-digit purebred line of Beijing fatty chicken backcrossed to Shiqiza chicken and by using restriction-site associated DNA based markers, we performed a genome-wide association study on the trait of polydactyly. Furthermore, whole genome resequencing strategy was applied to sweep SNPs across the whole genome. An outlier-based Fst approach was employed to search for signatures of selection, and results indicated that the determinant mutation was found in the region ranging from 8.3 Mb to 8.7 Mb, where the polydactyly candidate gene LMBR1 was located. The G/T mutation of rs80659072 was identified to be highly associated with polydactyly in our resequencing and was validated in random samples from an expanded population. Thus, we confirmed that LMBR1 was the causative gene of polydactyly in the Beijing fatty chicken by using GWAS with restriction-site associated DNA based markers and resequencing.